The Rectifying Contact of Hydrated Different Size YSZ Nanoparticles for Advanced Electronics - Alexander S. Doroshkevich; Anna S. Zakharova; Boris L. Oksengendler; Andriy I. Lyubchyk; Sergiy I. Lyubchyk; Svitlana B. Lyubchyk; Alisa A. Tatarinova; Andriy K. Kirillov; Tatyana A. Vasilenko; Oksana O. Gorban; Viktor I. Bodnarchuk; Nadejda N. Nikiforova; et al. (Nanomaterials, 2022)
The paper considers the new effects of the nanoscale state of matter, which open up prospects for the development of electronic devices using new physical principles. The contacts of chemically homogeneous nanoparticles of yttrium-stabilized zirconium oxide (ZrO2—x mol% Y2O3, x = 0, 3, 4, 8; YSZ) with different sizes of 7.5 nm and 9 nm; 7.5 nm and 11 nm; and 7.5 nm and 14 nm, respectively, was studied on direct current using nanostructured objects in the form of compacts obtained by high-hydrostatic pressure (HP-compacts of 300MPa). A unique size effect of the nonlinear (rectifying-type contact) dependence of the electrical properties (in the region U < 2.5 V, I ≤ 2.7 mA) of the contact of different-sized YSZ nanoparticles of the same chemical composition is revealed, which indicates the possibility of creating semiconductor structures of a new type (homogeneous electronics). The electronic structure of the near-surface regions of nanoparticles of studied oxide materials and the possibility of obtaining specifically rectifying properties of the contacts were studied theoretically. Models of surface states of the Tamm-type are constructed considering the Coulomb long-range action. The discovered energy variance and its dependence on the curvature of the surface of nanoparticles made it possible to study the conditions for the formation of a contact potential difference in cases of nanoparticles of the same radius (synergistic effect), different radii (doped and undoped variants), as well as to discover the possibility of describing a group of powder particles within the Anderson model. The determined effect makes it possible to solve the problem of diffusion instability of semiconductor heterojunctions and opens up prospects for creating electronic devices with a fundamentally new level of properties for use in various fields of the economy and breakthrough critical technologies.